2011
DOI: 10.1111/j.1744-7402.2010.02570.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Direct Microwave Sintering on Structure and Properties of 8 Mol% Y2O3-ZrO2

Abstract: Fully stabilized‐zirconia is proposed as an inert matrix for next‐generation nuclear fuels. This study presents the application of microwave technology for lowering the sintering temperature of 8 mol% yttria–zirconia (8YZ) to minimize the loss of volatile actinides that will be incorporated into the fuels. Direct microwave sintering results were compared with microwave‐hybrid and conventionally sintered samples. Direct Microwave Sintering of 8YZ showed a reduction of 300°C in temperature required for full dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…Numerous reports (as well as the work presented here) have shown an acceleration in densification and grain growth during microwave sintering [1,2]. Microwave heating is a conversion of electromagnetic energy to heat, mainly due to the formation and displacement of dipoles [3,4].…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Numerous reports (as well as the work presented here) have shown an acceleration in densification and grain growth during microwave sintering [1,2]. Microwave heating is a conversion of electromagnetic energy to heat, mainly due to the formation and displacement of dipoles [3,4].…”
Section: Introductionmentioning
confidence: 79%
“…The green pellets selected for this study were 46±5 % of the Theoretical Density (TD). The powder characterization, compaction, and sintering behavior (both conventional and microwave-assisted heating) of these powders have been reported previously [2,14].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mazaheri et al utilized the conventional sintering and microwave sintering to process nanocrystalline yttria-stabilized zirconia, and the results indicated the microwave-treated samples had the very fine grain sizes and macroscopic mechanical properties, exhibiting better microstructure uniformity [34]. Thridandapani et al reported a reduction of 300 °C in temperature for full densification of 8 mol% yttria-zirconia (8YZ) was achieved by direct microwave sintering compared with conventional sintering, and even 100 °C lower than microwave-hybrid sintering with no difference in resulting properties [35]. Microwave heating directly delivery the required energy to reaction atoms to form the unique mechanism of microwave heating, instead of the conventional heating through heat transfer process from the surface to inside [36][37][38], changing the gradient direction of some migration potentials during the conventional heating process, achieving the volumetric heating of the sample with a fast heating rate and uniform heating, further to cause the formation of a microscopic structure with small particle size and uniform distribution [39][40], rendering the excellent effects for zirconia ceramics materials by microwave sintering.…”
Section: Introductionmentioning
confidence: 99%